Software implementation of a pseudo-linear correction device with separate channels for amplitude and phase in industrial control - Zhenbei Li; Maksim V. Skorospeshkin (Известия Томского политехнического университета: Промышленная кибернетика)
The paper proposes an approach to improve the quality of control for a nonstationary system by incorporating an automatic control system with a pseudolinear corrective device with separate channels for amplitude and phase control. The corrective device enables independent adjustment of stability margins for both amplitude and phase, regardless of the input signal amplitude. The corrective device can also be adaptive, allowing real-time adjustment of its parameters to enhance control quality for nonstationary systems. The paper introduces a model of the automatic control system, featuring a second-order system with a PID controller and a pseudolinear corrective device. An example of a software implementation of the pseudolinear corrective device with separate amplitude and phase channels is provided using the Function Block Diagram (FBD) language on the CoDeSys 2.3 platform.